Calculation of High Pressure Heater Efficiency in the Feedwater System of PT PLN IP Teluk Sirih Unit 2 Steam Power Plant - Zulvani Adha; Andre Kurniawan; Arwizet K; Yolli Fernanda (Unversitas Negeri Padang, 2026)
PT PLN IP Teluk Sirih is a coal-fired steam power plant that supplies electricity to the West Sumatra region. In steam power plants, the High Pressure Heater (HPH) functions as a heat exchanger that preheats feedwater before entering the boiler by utilizing extraction steam from turbine. Damage or performance degradation of the HPH can reduce its effectiveness and lifespan, decrease feedwater temperature, increase the required heating in boiler, raise fuel consumption, and ultimately lower the overall efficiency of the power plant cycle. Therefore, this study aims to determine the efficiency of HPH at PT PLN IP Teluk Sirih Unit 2 in order to support proper maintenance planning and reduce operational costs. The research employs a quantitative method with a descriptive–analytical approach using actual operational data obtained from the Distributed Control System (DCS) of PLTU Teluk Sirih Unit 2. The efficiency of HPH is calculated by comparing the heat released by the steam and the heat absorbed by the feedwater or HPH 1 and HPH 2. The variables used include the feedwater inlet temperatures of 192.9 °C for HPH 1 and 141.5 °C for HPH 2. The results show that the efficiency of HPH 1 is 91.26%, while the efficiency of HPH 2 is 88.11%. For HPH 1, and are 49,552,500 kJ/h and 54,297,300 kJ/h, respectively, whereas for HPH 2, and are 71,613,300 kJ/h and 81,288,480 kJ/h. These results indicate that a higher inlet temperature leads to a greater ratio between and , and consequently to a higher HPH efficiency.